Mengokohkan Persaudaraan Melalui Nilai-Nilai Al-Qur’an: Studi Komparatif Tafsir Klasik dan Kontemporer - Fani Firda Yuniarti (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
The practice of the concept of brotherhood has recently been challenged by exclusive behavior. Brotherhood in its various forms, such as brotherhood based on shared beliefs, national brotherhood, and human brotherhood, is difficult to achieve because of this exclusivity. Brotherhood in the Qur'an has many contexts and scopes, namely brotherhood because of blood relations, kinship, religion, profession, and humanity. All of these contexts and scopes are beautifully intertwined. What is destructive is excessive pride in lineage, wealth, and territory, as well as unfairness and disrespect for human dignity due to differences in skin color and class. In this regard, this article examines the concept of brotherhood in the Qur'an, which is specifically explained in QS. Al-Hujurat: 10 and 13, as well as QS. Ali Imran: 103. In discussing these verses on brotherhood, the author uses a comparative method of interpretation al-Baghawi and al-Mizan. The reason for choosing these two interpretations is primarily to seek insights from classical and contemporary interpretations, as well as to capture two traditions of interpretation from different schools of thought. Based on the study of these two interpretations, it was found that in establishing and maintaining brotherhood, it is necessary to have mutual respect and fairness towards one another. There should be no sense of superiority, nor excessive pride in oneself, lineage, wealth, or race. The absence of fairness and mutual respect.